Formation and environmental significance of late Quaternary calcareous root tubes in the deserts of the Alashan Plateau, northwest China. (22nd June 2015) - Li, Zhuolun; Wang, Nai'ang; Cheng, Hongyi; Ning, Kai; Zhao, Liqiang; Li, Ruolan
Abstract: Calcareous root tubes are widely distributed across the Badain Jaran Desert and the Tengger Desert of the Alashan Plateau in northwest China. However, the reliability of their 14 C dating results and their environmental significance remain unclear. In this study, the conventional 14 C ages of 31 calcareous root tube samples and one aquatic mollusc shell sample, which were all collected from the Badain Jaran Desert and the Tengger Desert, were measured. The results reveal that nine of the 14 calcareous root tube samples from the Badain Jaran Desert were from Marine Isotope Stage (MIS) 3, while two samples were from MIS 2. The other three samples were dated to the mid-Holocene, one of which is consistent with the aquatic mollusc shell sample collected from the shoreline of Zhunzhahanjilin Lake in the Badain Jaran Desert. Moreover, the 17 calcareous root tube samples from the Tengger Desert were all dated to the mid- and late-Holocene, most of which were from the mid-Holocene. The results demonstrate that calcareous root tubes can be used as 14 C dating materials and that the accuracy of their 14 C dating depends on the time scale. The dating results were reliable at the millennial scale. However, the reliability of the ages from MIS 3a is lower than that of the Holocene ages, though the ages were reliable in tens of thousands years. Based on the statistical analysis, the overwhelming majority of calcareous root tubes collected from the deserts of the Alashan Plateau were formed during MIS 3a and the mid-Holocene. The concentrated emergence of calcareous root tubes in phases implies that they were formed during periods of relatively humid environments in desert areas, arid regions. Moreover, the results indicate that the effectivity of the moisture level probably affects the formation of calcareous root tubes, and the presence of calcareous root tubes indicates the occurrence of periods of relatively humid environments in the study area.